The Effect of the Implementation of Internal Green Supply Chain Management on Operational Flexibility, Delivery, Product Quality and Production Costs in Convection SME in Bogor City, Indonesia - Wong, Francisca Lutfia; Santosa, Wahyuningsih (Manunggal Halim Jaya, 2025)
This study aims to examine the effect of internal green supply chain management practices on operational flexibility, product quality, delivery efficiency, and production costs in convection SME in Bogor City. In the digital era and increasing awareness of sustainability, SME are required to adopt more environmentally friendly business practices to remain competitive. This study used a questionnaire method distributed to 153 respondents from convection SME in Bogor City. The results showed that the implementation of internal green supply chain practices had a significant effect on improving operational flexibility, product quality, and delivery efficiency, and was able to reduce production costs. These findings indicate the importance of integrating sustainability aspects in supply chain management to improve operational performance and competitiveness of SME.